Page Segmentation using XY Cut Algorithm in OCR Systems - A Review - Kaur, Sukhvir; Mann, P.S.; Kaur, Sukhwinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2007)
Page segmentation is an important field to analyse patterns from the OCR Systems. In this paper we tried to present how page segmentation is done on the OCR systems. We discussed the XY Cut page segmentation algorithm. The result of XY Cut page segmentation is evaluated on scanned OCR document.